Classroom management for middle and high school teachers - Emmer, Edmund T. (Pearson, 2009)
This guide for pre- and in-service middle and high school teachers gives guidelines for managing classroom space, activities, and student behavior. Some areas covered include rules and procedures, managing student work, problem behaviors, and managing special groups such as remedial classes and students with special needs. Each chapter includes activities and preparation checklists in a b&w format with classroom photos and familiar cartoon strips. A companion web site provides authentic classroom videos, interactive simulations on adapting instruction, case studies, selected journal articles, tools for creating and sharing lessons plans and portfolios, and access to news articles on education. This eight edition features a new introductory section offering an account of the authors' and others' classroom research supporting the book's recommendations.